Bronchoscopy/endobronchial ultrasound - Herth, Felix (Controversies in the treatment of Lung cancer, 2010)
Abstract. Endobronchial ultrasound (EBUS) has emerged as a new diagnostic tool that allows the bronchoscopist to see beyond the airway.